Quality Attributes Decision Modeling for Software Product Line Architecture - I Made Murwantara (UIN Sultan Syarif Kasim Riau, 2011)
Decision modeling is one of the most prominent activity for architecture design of a software product line architecture. The decision modeling supports the selection of suitable composition of software components from the architecture of member products of a product line. However, only little effort have been devoted to quality attributes. To address this shortcoming, this paper present a method that hybrid the Analytical Hierarchy Process and the Formal Concept Analysis. The key issue of decision modeling that assessing a quality attributes of an architecture configuration is to measure the impact of a quality attributes that made by the set of components. In this paper, we analyze the software components composition that corresponds to the quality attributes. An illustrative example based on the e-Learning software product line is presented to demonstrate of how the proposed approach works. Keywords: Software Product Line, Product Line Architecture, Decision Modeling, Analytical Hierarchy Process, Formal Concept Analysis, Software Architecture Design